Toward Smart Diagnostics in a Pandemic Scenario: COVID-19 - Hosseinifard, Mohammad; Naghdi, Tina; Morales-Narváez, Eden; Golmohammadi, Hamed (Frontiers in Bioengineering and Biotechnology, 2021)
The incredible spread rate of coronavirus disease 2019 (COVID-19) outbreak has shocked the world. More than ever before, this dramatic scenario proved the significance of diagnostics as a cornerstone to make life-saving decisions. In this context, novel diagnostics that generate smart data leading to superior strategies for treatment, control, surveillance, prediction, prevention, and management of pandemic diseases is vital. Herein, we discuss the characteristics that should be met by COVID-19 diagnostics to become smart diagnostics enabled by industry 4.0 especially Internet of Things (IoT). The challenges ahead and our recommendations for moving faster from pure diagnostics towards smart diagnostics of COVID-19 and other possible epidemic/pandemic diseases are also outlined. An IoT-Fog-Cloud model based on smartphones as IoT gateways for smart diagnostics with unified strategies for data collection/transmission/interpretation is also proposed to integrate new digital technologies into a single platform for smarter decisions. Last but not least, we believe that “smart diagnostics” is a perspective that should be realized sooner before we encounter a pandemic far worse than the present one.